Pengaruh Gaya Kepemimpinan, Motivasi, Dan Disiplin Kerja Terhadap Kinerja Pegawai Melalui Pengembangan SDM Pemerintah Daerah Provinsi Kepulauan Riau - Hidayat; Mursal; Yantri, One; Windayati, Diana Titik; Onoyi, Nona Jane (LPPM STIE KRAKATAU, 2023)
Leadership style, motivation in working and employee work discipline are classic problems faced by various organizations in achieving performance targets, therefore HR that continues to be developed is one of the keys so that the wheels of the organization run as expected, employees who do not feel comfortable at work, are unable to improve their careers, and work pressure is too heavy will not be able to carry out their responsibilities optimally. The current research is intended to see how much influence the leadership style, motivation, and work discipline have on employee performance through HR development within the Riau Islands Provincial Government with a population of 5,108 people, while the sample was taken 290 with the convenience sampling method, respondents were given a questionnaire distributed via the Google Form link with a data collection time of about one month, then the data was processed and analyzed further. Based on the results of data processing, it shows that the results of hypothesis testing on leadership style variables, motivation, work discipline, and HR development on employee performance have a significant effect, this is as shown in the t test results. The same results are shown in the F test, namely that there is a significant effect simultaneously on the variables of leadership style, motivation, work discipline, and HR development on employee performance variables. Next, in the results of the intervening variable hypothesis test, all regressions show a significant relationship between variables in accordance with the requirements. Furthermore, the test result of the adjusted R2 value is 0.615, which means that the variables of leadership style, motivation, and work discipline and HR development used in general are able to provide 61.5% of the influence on employee performance. However, this research still has many limitations, the number of samples is still too small from the population, the variables used are limited. Recommendations that can be taken into consideration in further research are in the selection of samples, especially for respondents, can be focused based on the OPD of the Riau Islands Provincial Government.